Recent levels and trends of fertility and mortality in Myanmar - Nyan Myint (Asia-Pacific Population Journal, 1991)
In Myanmar, the vital registration system was first introduced into some parts of Lower Myanmar in the late nineteenth century and gradually expanded to other parts of the country. It was introduced into the towns of Upper Myamnar in 1906 and the villages of Upper Myanmar in 1907 (Kyin, 1959, p. 6). By 1931, about 82.5 per cent of the population was covered by the registration system (United Nations, 1959, p. 47). In those days, vital statistics were collected by municipal health offices in urban areas and by village headmen in the rural areas. The reports were published by the Department of Public Health (Sundrum, 1957, p. 7).